(untitled) (Scientific journal of the Fergana State University, 2026)
This scientific work analyzes the pedagogical, psychological, and physiological significance of using active games in shaping physical qualities and developing motor skills in primary school students. The research results indicate that active games in physical education lessons as well as extracurricular activities are effective not only in promoting physical development but also in enhancing students’ motivation, emotional stability, creativity, and teamwork skills. Based on surveys and physical fitness tests conducted among 2nd–4th grade students, it was revealed that active games are insufficiently implemented in the existing educational process, workloads are not planned according to an individual approach, and monitoring of physical development is not systematically organized. In particular, experimental analyses conducted with 9-year-old students showed that their physical fitness levels were below the standards, which highlights the necessity of organizing physical education lessons in a phased and differentiated manner.